Learning and teaching at M-level : a guide for student teachers - Bryan, Hazel. (SAGE, 2010)
This text guides readers through the different aspects of doing M-level work at either primary or secondary stage, & helps to develop a deeper professional understanding. Chapters include primary & secondary vignettes & examples to link theory into practice, as well as questions, activities & suggestions for further reading.